Shear behaviour of a novel vertical grouting joint in precast concrete structure for wind turbines. (January 2023) - Wang, Yu-Hang; Luo, Wei; Zhou, Xu-Hong; Shuai, Fu-Wen; Ren, Wei; Tan, Ji-Ke
Highlights: A novel vertical grouting joint in precast concrete structure for wind turbines was proposed, and six specimens were designed and subjected to shear tests. A three-stage shear force model of the joints was proposed. The shear capacities of specimens were calculated using the existing design methods, and correspongding design suggestions were proposed. Abstract: Precast concrete structure (PCS) towers have been widely used as support structures for onshore wind turbines owing to their high stiffness, good stability, and low maintenance cost. Owing to the limitations of production, transportation and construction, the PCS towers must be vertically segmented, and the vertical segments of precast concrete are mainly connected by filling the joints with high-strength grouting materials (HSGMs). The shear performance of the vertical grouting joints significantly affects the mechanical behaviour of PCS towers for wind turbines. To study the shear performance of the vertical grouting joints of PCS towers, six vertical grouting joint specimens were designed and tested under shear loads, and the failure modes and shear force–slip curves of the specimens were examined. The experimental results indicated that the failure modes of the specimens involved the interface peeling failure of the new and old concrete and the shear failure of the HSGM. U-shaped shear reinforcement can increase the ultimate and residual shear capacities of joints and significantly improve the ductility of vertical grouting joints. Vertical reinforcement has a limited effect on the ultimate shear capacities of vertical grouting joints but can limit the development of internal cracks and improve the residual shear capacities of joints. According to the experimental results and force–slip curves of the specimens, the shear force mechanism of the joints was analysed, and a three-stage shear force model of the joints was proposed. Moreover, the distribution of shear strain on the concrete surface along the height of the specimens under different load levels was analysed. Finally, the shear capacities of all the vertical grouting joint specimens were calculated using the existing design methods, and correspongding design suggestions were proposed according to the calculation results.